331. Vascular Complications Among Children and Adolescents With Acute Complicated Sinusitis. (26th November 2018) - Troy, Elizabeth; Sillau, Stefan; Bernard, Timothy; Rao, Suchitra
Abstract: Background: The characteristics of intracranial vascular complications in children from bacterial sinusitis is not well known. The objectives of the study were to describe the types of vascular complications and pathogens in acute complicated sinusitis and identify the proportion of vascular complications due to Streptococcus anginosus vs. other pathogens. Methods: We conducted a retrospective cohort study by identifying hospitalized patients with ICD 9/10 codes of acute sinusitis at Children's Hospital Colorado from 2010–2016. After identifying patients with complicated sinusitis (bacterial meningitis, intracranial abscess/empyema, venous thrombosis, stroke, or orbital cellulitis/abscess based on ICD 9, ICD 10, or imaging findings), we reviewed patient demographics, clinical characteristics, and clinical outcomes. Patients with cultures positive for S. anginosus were compared with other patients who met inclusion criteria. Bivariable relationships were examined using χ 2 tests and t -tests or Wilcoxon rank-sum tests. Results: Among 416 inpatients with acute sinusitis, 235 had acute complicated sinusitis. Of these, 75 were excluded due to immunocompromised status, cystic fibrosis, craniofacial abnormality, and fungal disease. The most common pathogen was S. anginosus, identified in 64/160 (40%) cases. Vascular complications were observed in 21/160 (13%) children (Figure 1). The rate of vascular complications was higher in the S. anginosus group, compared with the non- S. anginosus group, although not reaching a statistical difference (18% vs. 9%, P = 0.085) The most common vascular complication was dural venous sinus thrombosis (30%). Children with S. anginosus infection were older (11.8 vs. 7.2 years), had an abnormal MRI (97% vs. 68%) and neurological deficit (56% vs. 35%), and required surgery (98% vs. 35%), longer antibiotic duration (42 vs. 16 days), and ICU admission (34% vs. 11%), P < 0.01 unless otherwise mentioned. Conclusion: Vascular complications among children with complicated sinusitis are common, with a high proportion due to S. anginosus . There is a greater burden of disease from S. anginosus compared with other bacterial pathogens as demonstrated by worse neurologic and radiographic outcomes in this group. Disclosures: All authors: No reported disclosures.